Risk Factors of Upper Limb Lymphedema after Breast Cancer Surgery in Women - Jinghui HUANG; Feng HUANG; Pei ZHU; Shuainan SHEN; Kefan CAO; Cheng LIU; Fanfu FANG; Bai LI (康复学报)
Objective:To investigate the incidence and risk factors of breast cancer-related lymphedema (BCRL) after surgery in women.Methods:A total of 246 female patients were selected with unilateral and single-focus breast cancer. The relevant medical history data were consulted, and the medical records of scientific research were completed, including general data of the patients (age, weight, payment method, culture level, complication, etc.), the tumor data (pathological type, stage, postoperative hormone receptor, the Her-2, number of lymph node dissection, number of positive lymph nodes, etc.) and the treatment data (surgery way, axillary lymph node processing way, whether to accept radiation therapy, whether to accept postoperative chemotherapy, chemotherapy program, chemotherapy cycles, whether to accept endocrine therapy, endocrine medication and medication time, etc.), establishing the clinical data bases of BCRL. BCRL evaluation was completed by means of the follow-up cases, and its severity was judged by the perception of self-symptoms in bilateral palms, forearms, upper arms and other parts in patients, by using the Norman Chinese version questionnaire. The clinical data were retrospectively analyzed, combined with the statistical factors associated with BCRL, onset age, preoperative BMI, follow-up BMI, operation method, operative side, number of lymph nodes dissected, positive lymph nodes, hypertension, diabetes, chemotherapy, radiotherapy and endocrine therapy, etc..Chi-square test was used for univariate analysis, and logistic regression analysis method was used for multiple factors analysis.Results:Forty-seven cases were diagnosed with BCRL, 199 cases were't diagnosed with BCRL and the incidence of BCRL at 1-3 years after surgery was 19.11%. All the cases were clearly diagnosed by pathology, including 136 cases with ER positive, 113 cases with PR positive and 161 cases with Her-2 positive. Only 31 cases in the whole group received breast-conserving surgery. In the univariate analysis of the influencing factors of BCRL, there were 9 factors including BMI, hypertension, postoperative chemotherapy, postoperative radiotherapy, postoperative endocrine therapy, number of lymph node dissection, positive lymph nodes and age of diagnosis, which were statistically significant differences between the edema group and the non-edema group. Multivariate analysis showed that hypertension (OR=11.868), postoperative chemotherapy (OR=6.669), radiotherapy (OR=3.408) and positive lymph nodes (OR=3.838) were risk factors for BCRL.Conclusion:BCRL is one of the serious complications after breast cancer surgery, for patients with hypertension, positive lymph nodes, receiving postoperative chemotherapy and radiotherapy, the health education and preventive measures should be actively carried out to avoid the occurrence of lymphedema.